Examining MOOCs: A Comparative Study among Educational Technology Experts in Traditional and Open Universities - Cabrera, Nati; Fernández-Ferrer, Maite (International Review of Research in Open and Distributed Learning, 2017)
The proliferation of Massive Open Online Courses (MOOCs) in recent years has generated much debate. MOOCs have been presented as technology-based educational practices, but many researchers question if this kind of open courses really respects some of the consolidated principles behind the education offered at universities. In light of this situation, consulting the teachers most closely tied to this type of course can provide an authoritative view of the issue and can allow the most important elements to be highlighted in order to carry out further research. Using a qualitative methodology based on an open questionnaire, this work presents the opinions and perceptions of teachers/lecturers in educational technology regarding these new courses key elements. These key elements are analysed through analysing its controversial definition, their pedagogical advantages and limitations, the functions of a tutor in a MOOC and their assessment (or accreditation). In addition, a comparison is made between the contributions of teachers from a traditional university with a face-to-face model and those from a distance university, which is based entirely on a virtual training offer and which has a greater possibility of coming into direct competition with these Massive Open Online Courses.